High-Temperature Stability of Natural Rubber Composites at High Temperatures in Short Time Ranges and Its Effect on Mechanical Properties. Issue 10 (2nd November 2022) - Li, Jia-Hao; Wan, Le; Deng, Cong; Gao, Xue-Qin
Abstract: Aircraft tires face extremely complex conditions during landing and the sharp temperature rise that is caused by the friction in a short period of time during landing may bring about serious destruction to the tread compound and thus threat on the safety of the aircraft. Our research described here focused on the high-temperature stability of a carbon black enhanced natural rubber (NR) composite at high temperatures (300-400 °C) in short time (0-100 s) ranges and its effect on the mechanical properties, and a deep investigation of the corresponding mechanisms. The experimental results confirmed that the thermal experience at 300-400 °C for 60 s did not remarkably affect the mechanical properties of the NR composite. However, serious damage to the mechanical properties of the NR composite occurred at 400 °C after thermal treatment for longer than 60 s. The analysis of the cross-linking density, hardness, and surface morphologies of the NR composite illustrated that the mechanical loss was related to the chemical and physical changes of the NR composite. Physical and chemical changes took place in the NR composites with increasing the heat treatment temperature, which seriously reduced the mechanical properties of the NR composites. Further analysis showed that more oxygen participated in the decomposition process of the NR with increasing the treating temperature from 300 to 400 °C, which led to more intensive decomposition of the NR and finally resulted in a remarkable decrease in mechanical properties of the NR composite.